Study on Properties of Walnut Protein Emulsion Modified by Limited Enzymatic Hydrolysis - CHEN Si-rui; HUANG Zi-lin; XING Ruo-yu; WANG Yu-qing; JIN Ya-mei; XU Xue-ming; KONG Xiang-zhen (Liang you shipin ke-ji, 2023)
The application of walnut protein is limited due to its poor water solubility and low yield. Five proteases, neutral protease, papain, bromelain, trypsin and protein glutaminase, were selected to carry out limited enzymatic hydrolysis reaction on walnut protein, and the modified walnut protein was applied to prepare the emulsion. The results showed that the solubility and emulsification of walnut protein were significantly improved after modification. Neutral protease modified protein (WP-Z) had the best emulsification and high stability. SDS-PAGE results showed that the macromolecular subunits of walnut protein were partially decomposed after limited enzymatic hydrolysis. After the modification, the particle size of the emulsion was reduced to 5~8 μm, and micro-volume of oil droplets was reduced. In addition, the dispersion was more uniform, and the emulsion index was greatly reduced, which did not exceed 10% in 30 days. By comprehensive analysis, the particle size of the emulsion prepared by WP-Z was moderate, which was more suitable for the preparation of emulsion.